Potential of untapped local species, “Chicha” (Stereospermum fimbriatum), as an alternative for skin infection treatment - Awang, Anis Fadhlina Izyani; Sarker, Md. Zaidul Islam; Ahmed, Qamar Uddin; Md. Jaffri, Juliana; Omar, Muhammad Nor (Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
Skin infection diseases are among the most common skin problems. Scientists believe that plants play a vital role in the public health. Stereospermum fimbriatum or “Chicha” used traditionally to cure stomachache, earache, itchy skin and postpartum illness. Therefore, this study was designed to investigate the phytochemical constituents of flowers, leaves, stem bark and twig of S. fimbriatum and their antimicrobial potential against eleven skin pathogens. Successive soxhlet extraction by n-hexane, dichloromethane and methanol was used. Disc diffusion, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were done to investigate their antimicrobial activities. Presence of terpenoid, steroid, flavonoid, saponin and tannin were observed in certain plant’s parts only. n-hexane extract of the S. fimbriatum’s stem bark (NS) possessed the most potent antibacterial activity especially against Staphylococcus epidermidis (16 mm±1), followed by MRSA (13.67 mm±0.58) and S. aureus (11.33 mm±0.58). All extracts exhibited no antimicrobial activity against Escherichia coli, Bacillus cereus, Pseudomonas aeruginosa, Proteus vulgaris, Enterococcus aerogenes, Candida albicans and Microsporum gypseum, except NS against S. pyogenes with weak antibacterial activity. The MIC analysis of susceptible strains resulted with a value of 1000 μg/mL. This study might lead to the discovery of novel agents with potential to treat dermal infections.